Penerapan Metode Mind Mapping Untuk Meningkatkan Berpikir Kritis Siswa Dalam Pembelajaran Ips - Aulia Tria Handari; Encep Supriatna (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The low student learning outcomes can’t be separated from the low students in critical thinking. During the learning process in the classroom, the teacher still has not implemented learning methods that encourage students to think critically. The teacher explains only through textbooks through lecture and assignment methods. The mind mapping learning method is a method used to remember through the help of pictures or colors with the aim that students are expected to be able to summarize the content of material that has a broad scope and also students can better understand the concept of a lesson. The mind mapping method at a glance will be shaped like tree branches, it makes it easier for the brain to store information such as how the brain works, so that the learning process in class becomes easier and students can think critically. The approach used in this study is a qualitative approach with Classroom Action Research (CAR) research methods. The subjects used in this study were students of class VI B SDN Cibodas 8 Tangerang City with a total of 16 students. To get the data, the researcher used observation, test, and documentation techniques. The data found based on the results of the percentage of students using mind mapping in the first cycle obtained a percentage of 46.25% and in the second cycle the percentage increased to 81.25% with a good category. Meanwhile, for the average value of the student's critical thinking test in the pre-cycle 49.68 in the first cycle increased to 61.87 then improvements were made so that in the second cycle the class average value increased to 79.86 with a good category. So that in this study the researchers concluded that the use of the mind mapping method for social studies learning found an increase in students' critical thinking in class VI.